The study of solid circulation rate in a compartmented fluidized bed gasifier (CFBG) - Wee, S.; Pok, Y.; Law, Ming; Lee, V. (2016)
Biomass waste has been abundantly available in Malaysia since the booming of palm oil industry. In order to tackle this issue, gasification is seen a promising technology to convert waste into energy. In view of the heat requirement for endothermic gasification reaction as well as the complex design and operation of multiple fluidized beds, compartmented fluidized bed gasifier (CFBG) with the combustor and the gasifier as separate compartments is proposed. As such, solid circulation rate (SCR) is one of the essential parameters for steady gasification and combustion to be realized in their respective compartments. Experimental and numerical studies (CFD) on the effect of static bed height, main bed aeration, riser aeration and v-valve aeration on SCR have been conducted in a cold- flow CFBG model with only river sand as the fluidizing medium. At lower operating range, the numerical simulations under-predict the SCR as compared to that of the experimental results. Also, it predicts slightly different trends over the range. On the other hand, at higher operating range, the numerical simulations are able to capture those trends as observed in the experimental results at the lower operating range. Overall, the numerical results compare reasonably well with that of the experimental works.